Wired to Change: The Role of Digital Messaging in Boosting EV Awareness Among Indonesian Millennials - Alicia Angelina Baso; Prida Ariani Ambar Astuti (Universitas Pelita Harapan, 2025)
In response to the global climate crisis, electric vehicles (EVs) have emerged as a sustainable alternative to gasoline-powered transportation. In Indonesia, PT PLN has leveraged Instagram to promote EV awareness among millennials. This study investigates the effectiveness of PLN’s digital messaging in enhancing awareness and shaping attitudes toward EVs. Using a quantitative survey method with 100 respondents aged 22–42, this research measures the relationship between message exposure, awareness, and attitude. Findings reveal that exposure to digital content significantly boosts both awareness and attitude, with awareness having a stronger impact. Regression analysis supports all four hypotheses, confirming that visual, informative, and relevant Instagram content leads to greater cognitive engagement and positive perception of EVs. The study underscores the role of social media in environmental communication, affirming the Elaboration Likelihood Model’s applicability in digital campaigns. These insights offer theoretical contributions to persuasion and consumer behavior studies, while also providing practical guidance for public-sector digital campaign strategies in emerging markets.